64.5k views
2 votes
9. Find the value of
the expression.
16 + 4 + (42 - 3) =

2 Answers

0 votes

Answer:

59

Explanation:

16 + 4 + (42-3) = 59. Do parentheses first. (42-3) = 39. Which changes the equation to 16 + 4 + (39). 39 + 4 = 43. Then the equation changes to 16 + 43. These added together equal 59. Hope this helps!

PEMDAS= Parentheses, exponents, multiplication, division, addition, and then subtraction.

This is the order in which to solve these types of equations, which is why I did the parentheses first.

User Robin Burchell
by
6.7k points
4 votes

Answer:

  • 59

Explanation:

  • 16 + 4 + (42 - 3) =
  • 20 + 39 =
  • 59
User Sqd
by
6.3k points